2016
DOI: 10.1111/jphp.12658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of localized interactions and surface properties on stability of protein-based therapeutics

Abstract: Physical and chemical stability of therapeutic proteins and antibody drug conjugates (ADCs) is of critical importance because insufficient stability prevents molecules from making it to market. Individual moieties on/near the surface of proteins have substantial influence on structure and stability. Seemingly small, superficial modification may have far-reaching consequences on structure, conformational dynamics, and solubility of the protein, and hence physical stability of the molecule. Chemical modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 125 publications
1
2
0
Order By: Relevance
“…It has been reported that Ile/Val can be used to substitute Cys to increase the thermostability of proteins. [84] These trends are correctly reflected in our analysis of amino acid compositions. Further, the charged residues such as Lys and Glu have a high frequency in the thermophiles than that in the mesophiles.…”
Section: Discussionsupporting
confidence: 68%
“…It has been reported that Ile/Val can be used to substitute Cys to increase the thermostability of proteins. [84] These trends are correctly reflected in our analysis of amino acid compositions. Further, the charged residues such as Lys and Glu have a high frequency in the thermophiles than that in the mesophiles.…”
Section: Discussionsupporting
confidence: 68%
“…A570 locates at the C-terminus of the protein, in the entrance of the active pocket (Figure a). Considering the protein nature of hydrophobic core and hydrophilic surface, , substitution of the solvent-exposed nonpolar side chain of alanine with polar ones could increase the physical stability of folded protein, leading to a more effective catalysis reaction. , According to the docking results, the hydrophilic groups −OH in substitution of Thr and −NH 2 in substitution of Asn were indeed exposed to the solvent (Figure b). In addition, considering its location at the entrance of the active pocket, the properties of the site 570 residue may influence the formation of the favorable chairlike binding conformation of DMAPP, thus affecting the elimination process of diphosphate group of DMAPP .…”
Section: Resultsmentioning
confidence: 99%
“…In general, the overall protein stability is determined by its residues and the interaction with its receptor and any alteration drastically affects its stability, interaction pattern, and thus the associated function. 26 Using a well-defined strategy for mutational analysis, we analyzed IL-15 pocket residues for their structural destability. Recently developed and more cited computational tools were used to tackle the challenging prediction of hotspots and their impact on the destability of the protein.…”
Section: Resultsmentioning
confidence: 99%